A Foundation Course in Reading German - Martin, Howard; Ng, Alan; Open Textbook Library (Open Textbook Library, 2017)
This textbook guides a learner who has no previous German experience to gain the ability to accurately understand formal written German prose, aided only by a comprehensive dictionary.
Introduction -- 1: Basics -- 2: Cases, present tense -- 3: Articles, simple past -- 4: Verbs with prefixes; adjective endings -- 5: Prepositions, reflexives -- 6: Conjunctions, comparatives -- 7: Perfect tenses and participles -- 8: Werden, relative clauses -- 9: Passive voice -- 10: Modal verbs -- 11: Infinitive usages -- 12: Da- compounds -- 13: Extended adjective constructions -- 14: Subjunctive I -- 15: Subjunctive II -- 16: Finishing touches -- ReferencePractice
In English.
Description based on online resource
Keywords: Humanities -- Textbooks; Language and languages -- Textbooks